Early prediction for over two years efficacy of the first biologic agent for polyarticular juvenile idiopathic arthritis: A multi-institutional study in Japan. Issue 5 (3rd September 2018) - Kubota, Tomohiro; Takei, Syuji; Shimizu, Masaki; Yasumura, Junko; Nakagishi, Yasuo; Kizawa, Toshitaka; Yashiro, Masato; Wakiguchi, Hiroyuki; Yamasaki, Yuichi; Kawano, Yoshifumi
Abstract: Objective: To estimate target of treatment for long-term efficacy of the first biologic agent used to treat polyarticular juvenile idiopathic arthritis (pJIA). Methods: A retrospective cohort of patients with pJIA treated at six medical institutions in Japan between 1 March 2005 and 31 October 2014 was identified. The patients were divided by 2-year treatment periods with the first biologic agent into continuous treatment group and switching group. Three markers were examined: matrix metalloproteinase-3 (MMP-3), erythrocyte sedimentation rate (ESR), and disease activity score (DAS) 28-ESR. Results: Thirty-two pJIA patients (8 boys, 24 girls) from 43 recruited patients were included in this study. The treatment periods with the first biologic agent in continuous treatment group (24 patients, 75%) was 40 months (median, range 24–119) and switching group (8 patients; 25%) was 9.5 months (median, 6–18). Markers [odds ratio (95% confidence interval)] at 3 months were MMP-3 [1.02 (0.99–1.05), p  = .219], ESR [1.00 (0.78–1.30), p  = .998], and DAS28-ESR [13.9 (2.08–409.82), p  = .035]. The cut-off point for DAS28-ESR at 3 months to distinguish the two groups was 2.49 (sensitivity, 87.5%; specificity, 87.5%). Conclusion: DAS28-ESR of 2.49 at 3 months after initiating the first biologic agent can be a target of sustained treatment in pJIA patients.